Reflections on the role of consultant radiographers in the UK: The perceived impact on practice and factors that support and hinder the role. Issue 1 (February 2016) - Henwood, S.; Booth, L.; Miller, P.K.
Abstract: Study context: This paper is the third paper arising from a two year long, in-depth case study exploring various components of the role of consultant radiographers in the UK. This paper focuses particularly upon the perceived impact of the role and factors that support and hinder the role in practice. Methods: A longitudinal case study method was used to explore the role of consultant radiographers. Interviewing was informed and guided by a phenomenological approach to promote a deeper understanding of consultants' experiences in the role. Eight consultant radiographers participated, with six involved throughout the whole study. Over an 18 month period each of those six consultants was interviewed three times. Two consultants only participated in the first interview; these interviews are also reported here. A total of 20 interviews were conducted. Findings: Interviews explored the impact of the consultant role as perceived by consultants themselves, and encouraged individual reflection on factors which had both supported and hindered success therein. Analysis demonstrated that there was substantial variation in the experiences communicated yet, and without any exception, all consultants reported that the introduction of their role had been beneficial to service delivery and quality of patient care. A number of obstacles were outlined, as well as a range of support mechanisms. Recommendations are thus made as to how the consultant role might be more effectively supported in the future. Highlights: The perceived impact of the consultant radiographer role in practice. Reflections upon what supported the consultants in their role. Reflections upon what hindered the consultants in their role.